Characteristics of Salmonella Recovered From Stools of Children Enrolled in the Global Enteric Multicenter Study. (25th January 2021) - Kasumba, Irene N; Pulford, Caisey V; Perez-Sepulveda, Blanca M; Sen, Sunil; Sayed, Nurulla; Permala-Booth, Jasnehta; Livio, Sofie; Heavens, Darren; Low, Ross; Hall, Neil; Roose, Anna; Powell, Helen; et al.
Abstract: Background: The Global Enteric Multicenter Study (GEMS) determined the etiologic agents of moderate-to-severe diarrhea (MSD) in children under 5 years old in Africa and Asia. Here, we describe the prevalence and antimicrobial susceptibility of nontyphoidal Salmonella (NTS) serovars in GEMS and examine the phylogenetics of Salmonella Typhimurium ST313 isolates. Methods: Salmonella isolated from children with MSD or diarrhea-free controls were identified by classical clinical microbiology and serotyped using antisera and/or whole-genome sequence data. We evaluated antimicrobial susceptibility using the Kirby-Bauer disk-diffusion method. Salmonella Typhimurium sequence types were determined using multi-locus sequence typing, and whole-genome sequencing was performed to assess the phylogeny of ST313. Results: Of 370 Salmonella- positive individuals, 190 (51.4%) were MSD cases and 180 (48.6%) were diarrhea-free controls. The most frequent Salmonella serovars identified were Salmonella Typhimurium, serogroup O:8 (C2 -C3 ), serogroup O:6, 7 (C1 ), Salmonella Paratyphi B Java, and serogroup O:4 (B). The prevalence of NTS was low but similar across sites, regardless of age, and was similar among both cases and controls except in Kenya, where Salmonella Typhimurium was more commonly associated with cases than controls. Phylogenetic analysis showed that these Salmonella Typhimurium isolates, all ST313, were highly genetically related to isolates from controls. Generally, Salmonella isolates from Asia were resistant to ciprofloxacin and ceftriaxone, but African isolates were susceptible to these antibiotics. Conclusions: Our data confirm that NTS is prevalent, albeit at low levels, in Africa and South Asia. Our findings provide further evidence that multidrug-resistant Salmonella Typhimurium ST313 can be carried asymptomatically by humans in sub-Saharan Africa. Abstract : In agreement with prior studies, we show that nontyphoidal Salmonella is prevalent in stool of children <5 years, albeit at low levels, in Africa and South Asia and Salmonella Typhimurium ST313 can be carried asymptomatically by humans in sub-Saharan Africa.